Institutional shelter: the social experiences of educators and adolescents - Silveira, Alcione Januaria Teixeira da; Nogueira, Marlice de Oliveira (Argumentum, 2024)
This article analyses the experiences of adolescents and educators in a shelter institution using François Dubet’s notion of social experience as its reference. The research was conducted using semi-structured interviews with adolescents and educators, documentary research, and a questionnaire answered by the shelter unit’s psychologist. The results show subjects giving meaning to their lived experiences and the ability to master their own lives. They are subjects of experiences constituted through cultural references, in and through activities regarding themselves. The institutionalisation of adolescents, despite is goal being to protect the rights of children and adolescents, contributes to reproducing and/or enhancing the social inequalities experienced and causes adolescents to disappear (in part) and to be affected by multiple processes of social exclusion.